Cost Analysis of Three Techniques of Administering Sevoflurane - Asha Tyagi; Vineeta Venkateswaran; Ajai Kumar Jain; Uttam Chandra Verma (Anesthesiology Research and Practice)
Background. This study aimed to evaluate and compare total cost of sevoflurane and propofol for 1.0 MAC-hour of anaesthesia, employing three anaesthetic techniques. Methods. Adult patients scheduled for surgical procedures under general anaesthesia anticipated to last approximately an hour were randomized into three groups (n=15 each), to receive anaesthesia using one of the following techniques: low flow technique involving induction with propofol, followed by sevoflurane delivered using initial fresh gas flows of 6 L/min till MAC reached 1.0 and then reduced to 0.5 L/min; alternate method of low flow entailing only a difference in fresh gas flow rates being maintained at 1 L/min throughout; the third technique involving use of sevoflurane for both induction and maintenance of anaesthesia. Results. Cost of sevoflurane to maintain 1 MAC-hour of anaesthesia was clinically least with low flow anaesthesia, though statistically similar amongst the three techniques. Once the cost of propofol used for induction in two of the three groups was added to that of sevoflurane, cost incurred was least with the technique using sevoflurane both for induction and maintenance of anaesthesia, as compared to low flow and alternative low flow techniques, a 26% and 32% cost saving, respectively (P<0.05).